2021
DOI: 10.1002/lrh2.10293
|View full text |Cite
|
Sign up to set email alerts
|

Developing real‐world evidence from real‐world data: Transforming raw data into analytical datasets

Abstract: Development of evidence-based practice requires practice-based evidence, which can be acquired through analysis of real-world data from electronic health records (EHRs). The EHR contains volumes of information about patients-physical measurements, diagnoses, exposures, and markers of health behavior-that can be used to create algorithms for risk stratification or to gain insight into associations between exposures, interventions, and outcomes. But to transform real-world data into reliable real-world evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 43 publications
0
24
0
1
Order By: Relevance
“…First, the problem of binary classification in patient persistence depends on the quality of the main classification label -that is, whether or not a given patient is persistent on the medication. This is derived from prescription, and there are known challenges in determining patient persistence from prescriptions [36], [37]. Whereas additional claims-based data sets could be used in conjunction with EHR data to improve the certainty of prescription patterns, that was not an available option during this work.…”
Section: Ehr Datamentioning
confidence: 99%
“…First, the problem of binary classification in patient persistence depends on the quality of the main classification label -that is, whether or not a given patient is persistent on the medication. This is derived from prescription, and there are known challenges in determining patient persistence from prescriptions [36], [37]. Whereas additional claims-based data sets could be used in conjunction with EHR data to improve the certainty of prescription patterns, that was not an available option during this work.…”
Section: Ehr Datamentioning
confidence: 99%
“…Multiple institutions across the USA maintain their own internal databases including some that are specific to the perioperative period. The challenges of using EHR data are well described and include technical barriers to access, lack of standardization, and varying quality of the data [24]. Nevertheless, EHR data are a valuable source of real-world practice insights and can aid machine learning, cross-sectional and longitudinal studies.…”
Section: Institution-specific Registries and Electronic Health Recordmentioning
confidence: 99%
“…OUD ICD codes tend to be associated with other psychiatric conditions, such as presence of other substance use disorders (i.e., alcohol and cocaine [41]), mood disorders and suicidality [42][43][44], and medical comorbidities, such as HIV and hepatitis C [42,45], as well as chronic pain, which has historically been one of the leading risks for initiating opioid misuse and is being addressed by initiatives such as the NIH HEAL Initiative [42,46]. However, ICD codes are assigned primarily for billing and administration purposes rather than research and are often not confirmed by a trained clinician [47]. Diagnostic codes are also binary and may not convey the severity of OUD phenotypes [48,49].…”
Section: Health Systems-based Cohortsmentioning
confidence: 99%
“…EHRs are heterogeneous, and data may be fragmented across different health systems or lost from lack of data collection (e.g., patient was never asked about opioid use) or lack of documentation (e.g., patient was asked about opioid use but the information was not recorded) [81]. However, some of these issues can be addressed by imputation methods [34, 47]. One limitation of these studies is that the results derived from particular health care systems are not necessarily generalizable (e.g., between cohorts that enroll participants based on disease status rather than those recruited from the general population [82]).…”
Section: Limitations Of Current Approachesmentioning
confidence: 99%